Speaking in thumbs : a psychiatrist decodes your relationship texts so you don't have to - Winsberg, Mimi (Doubleday, 2021)
"For readers of Maybe You Should Talk to Someone and Modern Romance, an essential look at the love language of text, helping you decipher the personalities of online daters, the subtle signals from your romantic partner, and the red flags hiding in plain sight When it comes to modern relationships, our thumbs do the talking. We swipe right into a stranger's life, flirt inside text bubbles, spill our hearts onto the screen, use emojis to convey desire, frustration, rage. Where once we pored over love letters, now we obsess over response times, or wonder why the three-dot ellipsis came . . . and went. Nobody knows this better than Dr. Mimi Winsberg. A Harvard and Stanford-trained psychiatrist, she co-founded a behavioral health startup while serving as resident psychiatrist at Facebook. Her work frequently finds her at the intersection of Big Data and Big Dating. Like all of us, Winsberg has been handed a smart phone accompanied by the urgent plea: "What does this mean?" Unlike all of us, she knows the answer. She is a text whisperer. Speaking in Thumbs is a lively and indispensable guide to interpreting our most important medium of communication. Drawing from of-the-moment research and a treasure trove of real-life online dating chats, including her own, Winsberg helps you see past the surface and into the heart of the matter. What are the telltale signs of deception? How do we recognize pathology before it winds up at our front door? How can we draw out that important-but-sensitive piece of information--Do you want kids? Do you use drugs? Are you seeing someone else?--without sending a potential partner heading for the hills? Insightful, timely, and impossible to put down, Speaking in Thumbs is an irresistible guide to the language of love. With wit and compassion, Winsberg empowers you to find and maintain real connection by reading between the lines"--